2011
DOI: 10.1088/2041-8205/732/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

Progressively More Prolate Dark Matter Halo in the Outer Galaxy as Traced by Flaring H I Gas

Abstract: A galactic disk in a spiral galaxy is generally believed to be embedded in an extended dark matter halo, which dominates its dynamics in the outer parts. However, the shape of the halo is not clearly understood. Here we show that the dark matter halo in the Milky Way Galaxy is prolate in shape. Further, it is increasingly more prolate at larger radii, with the vertical-to-planar axis ratio monotonically increasing to 2.0 at 24 kpc. This is obtained by modeling the observed steeply flaring atomic hydrogen gas l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 27 publications
5
41
1
Order By: Relevance
“…If we believe the halo is well represented by an axisymetric logarithmic potential with velocity normalisation v0 between 210 and 250 kms −1 , then the flattening equation implies that the axis ratio of the equipotentials q satisfies 1.5 q 2. This result is consistent with the claim of Banerjee & Jog (2011), who argued for prolateness based on an analysis of the HI flaring gas layer from 8 to 24 kpc.…”
Section: Discussionsupporting
confidence: 92%
“…If we believe the halo is well represented by an axisymetric logarithmic potential with velocity normalisation v0 between 210 and 250 kms −1 , then the flattening equation implies that the axis ratio of the equipotentials q satisfies 1.5 q 2. This result is consistent with the claim of Banerjee & Jog (2011), who argued for prolateness based on an analysis of the HI flaring gas layer from 8 to 24 kpc.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that it is difficult to reproduce the flaring within the context of spherical halo models (Narayan et al, 2005;Kalberla et al, 2007). Banerjee and Jog (2011) find that the flaring can be reproduced by a prolate dark matter halo that becomes the most prolate at ∼ 25 kpc, q 2.…”
Section: The Tilt Angles In Equation 33mentioning
confidence: 81%
“…In such a situation it is however difficult to measure the gas velocity dispersion σg, which is a critical parameter for the model. Banerjee & Jog (2011) show that the uncertainty in σg is an important contributor to the uncertainty in the scale-height computed from the model. The calculated HI scale-height is highly sensitive to the assumed value of σg; a 10% change in σg can lead to ∼ 15% change in the calculated HI scale-height.…”
Section: Introductionmentioning
confidence: 92%
“…Further, since the HI disc generally extends to galacto-centric radii where the gravity due to stars is negligible, both the flaring of the HI disc as well as its rotational velocity can be used as diagnostic probes of the underlying potential of the dark matter halo (see e.g. Olling 1995;Becquaert & Combes 1997;Narayan, Saha, & Jog 2005;Banerjee & Jog 2008;Banerjee, Matthews, & Jog 10;Banerjee & Jog 2011). While modelling of the vertical distribution of the gas can be used to infer the properties of the dark matter distribution, comparison of models with observations is complicated by the following problem.…”
Section: Introductionmentioning
confidence: 99%